The Use of Quizizz Application in Understanding Structure Course, University of Indraprasta PGRI Jakarta - Tita Puspitasari (STKIP PGRI Tulungagung, 2024)
The purpose of this research is to find out whether the use of the Quizizz Application is effective or not in teaching Understanding Structure/English grammar course on the student to fifth semester in Indraprasta PGRI Jakarta. The type of research used is literature/library study and observation through interviews with students.The results obtained the that application of Quizizz media it is very good and effective because using Quizizz media can increase student learning motivation because in Quizizz media it takes time and time that can be determined by the teacher in answering quizzes so that students can focus on working on and with the media Learning quizzes are interesting and not monotonous so that students don't get bored.